Premio Senior: Resultados de la cirugía endoscópica endonasal y predictores de evolución en la enfermedad de Cushing. Análisis de una serie de 40 casos. - Melgarejo, Ana; Guitelman, Mirtha; Tubert, Gloria; Figurelli, Silvina; Lescano, Sebastian; Guevara, Martín (Revista Argentina de Neurocirugía, 2022)
Objective: To evaluate the surgical results and predictors of remission in a series of 40 patients with Cushing’s disease (CD) undergoing endonasal endoscopic surgery (EEC) and compare them with the literature. Introduction: CD is caused by a corticotropic adenoma and has a high morbidity and mortality. The treatment of choice is transsphenoidal resection, with CEE proving in recent years to be a safe and effective alternative. Methods: The database of patients with CD operated on between January 2010 and December 2021 was retrospectively analyzed. The clinical, endocrinological, radiological, surgical, histopathological features and the outcomes of the patients were evaluated on, and two stages were compared. (first 20 surgeries vs last 20). Results: 32 women and 8 men underwent surgery, mean age 38.9 years. 21 microadenomas and 19 macroadenomas were operated on. Postoperative remission was obtained in 82.5% of the cases, finding a statistically significant association (p=0.00) with postoperative cortisol ≤ 1.8 µg/dl and with non-invasive tumors of the Knosp classification. In the second stage, a higher percentage of postoperative cortisol ≤ 1.8 µg/dl (73.7% vs 26.3%) and a higher percentage of remission (95% vs 70%) were obtained. The complication rate was 20%, with no mortality. 5 (15%) patients presented recurrence. With adjuvant treatment, 37 (92.5%) patients are in biochemical remission. Conclusion: CEE is the treatment of choice for CD, offering high remission rates with low morbidity. Predictive factors for remission were postoperative hypocortisolemia, noninvasive adenomas, and the experience of the surgical team.